PHOTOCATALYTIC DEGRADATION OF INDIGO CARMINE BY TiO2/ACTIVATED CARBON DERIVED FROM WASTE COFFEE GROUNDS - Irwan Irwan; Surya Lubis; Muliadi Ramli; Sheilatina Sheilatina (Universitas Syiah Kuala, 2016)
TiO2/activated carbon derived from waste coffee grounds (TiO2/WCGAC) has been prepared by a sol gel method . Waste coffee ground was chemically activated using hydrochloric acid 0.1 M solution and modified with titanium tetraisopropoxide as TiO2 precursor. The structural features of the photocatalyst was investigated by X-ray diffraction (XRD), scanning electron microscope energy dispersive X-ray spectroscopy (SEM EDX), Fourier transform infrared spectroscopy (FT-IR) and nitrogen adsorption-desorption. The XRD results showed that TiO2 is anatase and rutile phase, while FTIR spectra confirmed the presence of Ti-O groups. The specifics surface area of TiO2/WCGAC was higher than that of activated carbon derived from waste coffee grounds. The photocatalytic activity of TiO2/WGCAC has been evaluated for degradation of indigo carmine solution under UV and solar light irradiation. It was found that degradation percentage of indigo carmine under solar light was higher than that of under UV light.